Hypoxia-Inducible Factor-2α as a Novel Target in Renal Cell Carcinoma (Journal of Kidney Cancer, 2021)
Hypoxia-inducible factor (HIF), an important mediator of hypoxia response, is implicated in tumorigenesis in the setting of pseudohypoxia, such as in the inactivation of von Hippel–Lindau tumor suppressor protein (pVHL), leading to development and progression of clear cell renal cell carcinoma (ccRCC). Targeting downstream molecules in HIF pathway, such as vascular endothelial growth factor (VEGF), has led to improvement in clinical outcome for patients with advanced ccRCC, but such therapy thus far has been limited by eventual resistance and treatment failure. Following the discovery of HIF-2α playing a key role in ccRCC carcinogenesis, inhibitors targeting HIF-2α have been developed and have demonstrated encouraging efficacy and safety profile in clinical trials. This review discusses HIF-2α as a promising therapeutic target for ccRCC.